What Is the Impact of NERICA Rice on Yields and Nutrition in Sierra Leone? Evidence from a Randomized Control Trial - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
Innovations for Poverty Action (IPA) (https://www.poverty-action.org/), in partnership with the International Rescue Committee (IRC) (https://www.rescue.org/) and the Sierra Leone Agricultural Research Institute (http://www.slari.gov.sl/), conducted a randomized controlled trial (RCT) of NERICA-3 (an upland rice variety) in five districts of Sierra Leone to assess the effects on farmers’ yields and child nutrition.